South Sudan Economic Update, February 2020 : Poverty and Vulnerability in a Fragile Environment - World Bank (World Bank, Washington, DC, 2020)
After contracting for four consecutive years since FY2014/15, the economy is estimated to have recovered with a growth rate of 3.2 percent in FY 2018/19. These developments reflect activity in the oil sector, which rebounded strongly, and dividends from the peace agreement, which led to a reduction of hostilities in some regions across the country, leading to a mild recovery in a few non-oil sectors. Growth in the oil and mining sectors was estimated at 10.7 percent, services sector is estimated to have grown by 0.4 percent, and agriculture is estimated to have contractedby 2.5 percent. The oil-led growth may have limited impact on the welfare of most citizens as relatively little of it trickles down and very little is spent on basic service delivery. Slow growth in the non-oil sectors, coupled with limited expenditure on service delivery, and limited linkages between the oil and non-oil economy creates a disconnect between the observed oil-led growth and citizen welfare. Recent budget execution reports indicate that the social sectors not only get smaller allocations, they are also faced with under execution. The economy is still beset with high inflation and a soaring foreign exchange rate premium. The rate of inflation is estimated to have increased from 40 percent in December 2018 to 86 percent in June 2019, reversing the downward trend observed in the first half of FY2018/19. By October 2019, inflation is estimated to have risen to 170 percent. At the same time, the gap between the official exchange rate and the parallel market rate remains high, indicating that the official rate is overvalued and does not reflect the underlying economic fundamentals. While the increase in oil production and prices coupled with an improved outlook for a peaceful settlement initially led to a marked decline in the premium in the second half of 2018, this gap has been widening in the first half of 2019 and increased from 65 percent in December 2018 to 95 percent in September 2019.